Unjuk Kerja Purwarupa Sistem Pengatur Suhu dan Kelembaban Otomatis di Kebun Oka Jamur Bali - Kresna Hadi Wijaya; I Nyoman Setiawan; I Wayan Sukerayasa (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
Oka Jamur Bali is one of the oyster mushroom cultivation farmers. Lack of efficiency in regulating temperature and humidity in mushroom barns is an important factor in the growth of mushroom fruiting bodies. This condition requires an innovative solution to regulate and monitor temperature and humidity in the barn area. This research aims to build a prototype using Arduino UNO, ESP32, DHT11, pump and Internet of Things (IoT) technology. The monitoring system design uses Arduino UNO, NodeMCU ESP32, DHT11 and DC pump with 12V voltage. Arduino UNO functions as a control system to manage and control the temperature and humidity parameters of the mushroom barn environment with the DHT11 sensor used to accurately measure temperature and humidity. The combination of NodeMCU ESP32 and Arduino UNO aims for monitoring through the ThingSpeak platform which can be accessed with a smartphone connected to the internet network. Based on the results of the prototype of the automatic temperature and humidity control system, the system is able to measure the environmental conditions of the mushroom barn with humidity measurement results in the range of 79% - 82% and the average temperature during the test reached 29.35°C. The application of the system was able to reduce the temperature by 2.28% with an average temperature of 28.19°C and increase the relative humidity by 6.27% with an average humidity of 81.1% in the mushroom barn area. The results of income between the income generated by using the automatic temperature and humidity control system tool and the income of farmers without using the tool increased by Rp. 16,416.